Improvement Of The Community's Reading Literature Culture Through The Alfata Reading Home Belonged To Baroh Village Society - Nanda Saputra; Heri Kurnia (CV. Inara, 2021)
Technology and communication advancements have led in a decline in people's reading habits. It is necessary to conduct an activity that educates individuals about the benefits of family reading habits. The function of the school in fostering a reading literacy culture is not exclusive; it may be played by the community as well. The Reading House was founded with the assistance of institutional funding, corporate and religious donations, and community funds. The objective of this research is to detail numerous initiatives made by Alfata Reading House to enhance reading literacy culture. Alfata Reading House, Baroh Village, Pidie District, Pidie Regency, Aceh Province. This research was done at the Alfata Reading House, Baroh Village, Pidie District, Pidie Regency, Aceh Province. A qualitative descriptive study was employed to conduct this research. Data collecting methods included interviewing and observing. According to the procedures and strategies utilized for data collecting. Meanwhile, observations were made about the development of a reading literacy culture inside the Baroh Village community through the Alfata Reading House. This study made use of the following data analysis techniques: data reduction, data visualization, and conclusion drawing. The study's findings indicate that the Alfata Reading House routinely welcomes Nadhlatul Ulama schools in the Pidie area, connects with Nadhlatul Ulama branch leadership, and collaborates with parents.